(untitled) (Studia theodisca, 2023)
The essay takes a systematic look at some perspectives on the study of Giosue Carducci’s relations with German culture, offering a review of the research until today, examples of case studies, and a reflection on possible future research perspectives. Among the various areas addressed is that of the study of Carducci’s translations from German, with remarks on Carducci’s role in the transfer processes between Italy and Germany. Among other things, emphasis is given to the relevance of investigations into translations not yet published in the National Edition of Carducci’s Works. The last paragraph of the essay gives an account of a first census of Carducci’s autographs that have become part of German, Austrian and Swiss collections. In particular, prominence is given to autographs now preserved at the Fondation Martin Bodmer (Cologny, Genève): a manuscript of the ode Su Monte Mario (whose traces had been completely lost) and a still-unknown autograph of the poem Per la proclamazione del regno d’Italia.